Preparation and application of FeS-loaded alginic acid derived carbon shell coated Fe3O4 cathode
The Fe3O4 cathode is wrapped by FeS-loaded alginic acid-derived carbon shell, which solves the problems of catalyst deactivation and low reaction rate in heterogeneous electric Fenton, and achieves efficient H2O2 generation and pollutant removal, broadens the scope of pH application and improves the Stability and reusability of catalysts.
Patent Information
- Application Number
- CN202310724391.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-06-19
AI Technical Summary
In the existing heterogeneous electroFenton technology, the catalyst surface is easily deactivated by oxidation, and the Fe2+ dissolution is hindered, resulting in low reaction rate, low H2O2 yield and poor catalyst reuse ability, especially under alkaline conditions, the iron-based catalyst is seriously deactivated. Limits its application.
FeS-loaded alginic acid-derived carbon shell is used to wrap Fe3O4 (FeS/Fe3O4@C) cathode, and through the multi-reactivity center and the interface composite structure of FeS and Fe3O4@C, it promotes O2 adsorption and conversion, regulates the reaction pH, and reduces iron dissolution. Improve catalyst stability and H2O2 generation efficiency.
It realizes efficient production of H2O2 at a lower electric potential, broadens the scope of pH application, significantly improves the stability and reusable performance of the catalyst, reduces iron dissolution and operation costs, and improves pollutant removal efficiency.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the fields of materials and environment, and in particular to a method for preparing a FeS-loaded Fe3O4 cathode wrapped with an alginate-derived carbon shell and an application thereof in heterogeneous electro-Fenton. Background Art
[0002] As a new electrochemical advanced oxidation technology, the heterogeneous electro-Fenton advanced oxidation technology produces H2O2 in situ through a two-electron redox reaction at the cathode, and uses iron-containing materials as heterogeneous catalysts to provide Fe 2+ In recent years, the cathode electro-Fenton method, which has been developing in the field of water treatment technology, loads the Fenton catalyst to the cathode, avoiding the recovery of the catalyst and effectively reducing the formation of iron sludge. However, the catalyst surface is easily deactivated by oxidation, and Fe 2+ The dissolution of is hindered, which greatly limits the reaction rate of heterogeneous electro-Fenton. The iron-based catalysts currently under development use heterogeneous catalysts as electro-Fenton cathodes. At the cathode, oxygen produces H2O2 through reduction reaction. At the same time, the active sites in the iron-based catalysts decompose H2O2 to produce free radicals to degrade pollutants. However, this technology still faces certain challenges. Many catalysts show a four-electron water production process, and the iron dissolution is large, resulting in a reduction in the catalyst's ability to be reused.
[0003] The dual-functional cathode can produce H2O2 and catalytically degrade pollutants at the same time, which can further improve the utilization efficiency of H2O2 and the recyclability of the catalyst. However, it still faces the problems of high cathode potential, low H2O2 production, and large iron dissolution. In addition, conventional cathode electro-Fenton catalysts such as Fe2O3, Fe3O4, and FeOOH are easily deactivated under alkaline conditions. Therefore, it is of great environmental significance to construct cathode electro-Fenton catalysts applicable to a wide pH range. Among the catalyst preparation methods currently developed, wrapping a layer of carbon shell on the surface of the catalyst to construct a core-shell catalyst can effectively reduce the dissolution of the Fe-based core and improve the stability of the catalyst. However, the method of constructing an iron-based core-shell Fenton catalyst mainly involves pyrolyzing iron-based MOFs or embedding the catalyst in a carbon aerogel electrode, which has problems such as high raw material cost, complex synthesis process, and poor catalyst stability, which limits its actual industrial application. Heteroatom-doped porous carbon nanomaterials with unique structure and chemical composition were synthesized by utilizing the characteristics of natural biomass. These biomass-derived functionalized carbon nanomaterials have the advantages of strong conductivity, rich heteroatoms, high specific surface area, and large pore volume, and have broad application prospects in the field of electrochemistry. Summary of the invention
[0004] The present invention mainly aims at the problems existing in the current electro-Fenton, such as low H2O2 selectivity of the electrocatalytic cathode, poor catalyst stability and reaction limitation by pH, and aims to provide a green, environmentally friendly, low-cost, high-catalytic-activity and strong-stability FeS-loaded alginate-derived carbon shell-wrapped Fe3O4 cathode (FeS / Fe3O4@C), and apply it to heterogeneous electro-Fenton water treatment to achieve efficient H2O2 production and effective removal of pollutants at a relatively low potential.
[0005] The technical principle of treating sewage is: the multi-reaction active centers among C, O, S, and Fe components and the composite structure of FeS and Fe3O4@C interface can not only promote the adsorption and conversion of O2, but also significantly improve the overall activity of the catalyst. The principle of treating organic matter is: the FeS / Fe3O4@C modified cathode can in situ electrosynthesize H2O2 through a 2-electron reduction reaction of oxygen in the air. The cathode has high H2O2 synthesis efficiency and low energy consumption. The generated H2O2 can be encapsulated by Fe3O4 and Fe≡ in the FeS on the catalyst surface. 2+ Catalyzed Fenton reaction • OH and Fe 3+ , while under moderate alkaline conditions, H2O2 reacts with Fe on the catalyst surface 2+ The reaction generates Fe IV O 2+ and water; in addition, O2 is also reduced to • O2 − , further generating 1 O2, thereby achieving the co-catalytic degradation of pollutants by multiple active species. The FeS in the present invention can regulate the pH of the reaction system, thereby broadening the pH application range, and the core-shell encapsulation structure formed by the catalyst can reduce iron dissolution and achieve high reusability.
[0006] The specific method of the present invention is: Specifically, the preparation method of the FeS-loaded alginate-derived carbon shell wrapped Fe3O4 (FeS / Fe3O4@C) cathode of the present invention and its application in heterogeneous electro-Fenton water treatment technology include the following steps: 20 g / L sodium alginate and carbon black were mixed and stirred evenly at a mass ratio of 5:1 to 20:1, and then added into a 20 g / L ferrous sulfate heptahydrate solution at a volume ratio of 1:2, and the obtained composite gel was freeze-dried at a temperature of -40 °C; Furthermore, the obtained composite gel was placed in a tubular furnace under an inert gas atmosphere for pyrolysis, the temperature was increased to 400 °C at a rate of 3-5 °C / min, and the temperature was kept constant for 1.5-2.5 h, and then the temperature was increased to 800 °C at a rate of 8-12 °C / min, and the temperature was kept constant for 1.5-2.5 h to obtain the FeS-loaded alginate-derived carbon shell-wrapped Fe3O4 catalyst FeS / Fe3O4@C.
[0007] Furthermore, the obtained FeS / Fe3O4@C catalyst powder was weighed into a mixed solution of ethanol and water in a ratio of 1:1, and 20% PTFE emulsion was added and shaken to mix evenly, and the loading amount was controlled to be 15-20 mg cm -1 Loaded on the substrate electrode, after natural drying, calcined in a tube furnace at 360 ° C for 30 min, it can be used as a cathode; adjust the pH of the wastewater to be treated to 3-11.
[0008] The present invention has the following outstanding features and beneficial effects: (1) The catalyst is simple to prepare, has a high yield, and exhibits a H2O2 selectivity of more than 90% and extremely low iron dissolution (<0.2 mg L -1 ) characteristics; (2) The catalyst exhibits multiple reactive active centers and structural features such as the interface composite between FeS and Fe3O4@C, which can effectively promote the electron transfer rate on the catalyst surface and Fe 2+ The FeS formed on the surface can provide a beneficial pH environment for electro-Fenton through reaction, thus broadening the pH application range. (3) The cross-linking effect between sodium alginate biomass, metal ions and carbon black is used to ensure a strong covalent bond between graphite carbon and metal catalytic components in the final product, thereby improving the heterogeneous electro-Fenton catalytic performance by promoting electron transport; (4) By using FeS / Fe3O4@C modified carbon felt as the cathode, it can ensure the continuous in-situ generation of H2O2 during the reaction process without the need for additional addition, thus solving the problems of H2O2 transportation and storage, and significantly reducing the operating cost; (5) The biomass raw materials used in the present invention are widely available and low in cost. The reaction operation is simple and the conditions are easy to control. The heterogeneous electro-Fenton process can achieve efficient removal of pollutants in the pH range of 3-11, and its reusability can reach more than 10 times, which has good practical application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 This is the X-ray photoelectron spectrum of the FeS / Fe3O4@C catalyst prepared in the present invention; Figure 2 This is a transmission electron microscope image of the FeS / Fe3O4@C catalyst prepared in the present invention; Figure 3 The effect diagram of the FeS / Fe3O4@C catalyst prepared by the present invention with a mass ratio of sodium alginate to carbon black of 10:1 and applied to the in-situ degradation of 50 mg / L tetracycline in a heterogeneous electro-Fenton process; Figure 4 This is a diagram showing the effect of the FeS / Fe3O4@C cathode prepared by the present invention with a mass ratio of sodium alginate to carbon black of 10:1 on the degradation of tetracycline at different pH values; Figure 5 The effect diagram of the FeS / Fe3O4@C catalyst prepared by the present invention with a mass ratio of sodium alginate to carbon black of 5:1 and applied to the heterogeneous electro-Fenton process for in-situ degradation of 50 mg / L tetracycline; Figure 6 The effect diagram of the FeS / Fe3O4@C catalyst prepared by the present invention with a mass ratio of sodium alginate to carbon black of 20:1 and applied to the heterogeneous electro-Fenton process for in-situ degradation of 50 mg / L tetracycline; Figure 7 The H2O2 selectivity diagram of the FeS / Fe3O4@C catalyst prepared by the present invention with a mass ratio of sodium alginate to carbon black of 10:1 and the control group; Figure 8 The effect diagram of the FeS / Fe3O4@C catalyst prepared by the present invention with a mass ratio of sodium alginate to carbon black of 10:1 and a control group applied to the heterogeneous electro-Fenton process for in-situ degradation of 50 mg / L tetracycline; Fig. 9 The hydroxyl radical and singlet oxygen diagram generated by the FeS / Fe3O4@C cathode prepared by the present invention; Fig.10 This is a diagram showing the effect of the FeS / Fe3O4@C cathode prepared in the present invention on the PMSO2 conversion rate during PMSO degradation at different initial pH values; Fig.11 This is a diagram showing the effect of the FeS / Fe3O4@C cathode prepared by the present invention being reused 10 times to degrade tetracycline; Fig.12 This is a diagram showing the effect of iron dissolution after the FeS / Fe3O4@C cathode prepared in the present invention is reused 10 times. Implementation
[0010] The present invention is further described in detail below by specific embodiments, examples of which are shown in the accompanying drawings. The embodiments described below with reference to the drawings are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0011] A mixed solution of sodium alginate and carbon black in a mass ratio of 10:1 was added dropwise to a ferrous sulfate heptahydrate solution, and the obtained composite gel was cold-dried at -40 °C for 24 h; the obtained composite gel was placed in an inert gas atmosphere, heated to 400 °C at a rate of 3-5 °C / min, and kept at this temperature for 1.5-2.5 h, and then heated to 800 °C at a rate of 8-12 °C / min, and kept at this temperature for 1.5-2.5 h to obtain an alginate-derived carbon shell-wrapped Fe3O4 catalyst loaded with FeS (FeS / Fe3O4@C).
[0012] Implementation Case 1 The components and properties of FeS / Fe3O4@C catalyst were characterized by X-ray photoelectron spectroscopy. Figure 1 The catalyst mainly includes C, O, S and Fe elements. The multilayer structure of FeS / Fe3O4@C was observed by transmission electron microscopy, which proves that the structure of the bifunctional catalyst is Fe3O4-loaded FeS particles wrapped by alginate-derived carbon shell (see Figure 2 ).
[0013] Implementation Case 2 The catalytic performance test of FeS / Fe3O4@C cathode in this example is as follows: 200 mL of 50 mg L -1 Tetracycline was dissolved in 50 mM sodium sulfate solution at pH 7. When the loading amount of FeS / Fe3O4@C was 0.02 g cm -2 , at a cathode potential of -0.4 V (vs reversible hydrogen electrode), Figure 3 It can be seen that when the mass ratio of sodium alginate to carbon black is 10:1, 98% of tetracycline can be removed after 2 hours of reaction.
[0014] refer to Figure 4 When the solution pH is 3-11, the system can show more than 80% tetracycline removal, and the best result is shown at pH = 3. At the same time, at pH 5 and 7, the removal of tetracycline is not much different, indicating that the FeS / Fe3O4@C cathode is more advantageous under moderately alkaline conditions.
[0015] Implementation Case 3 The steps of implementation case 3 are basically the same as those of implementation case 1, except that FeS / Fe3O4@C with a mass ratio of sodium alginate to carbon black of 5:1 was prepared. When this catalyst was used as the cathode, the removal of tetracycline was 79% in 2 hours. The results are shown in Figure 5 .
[0016] Implementation Case 4 The steps of implementation case 3 are basically the same as those of implementation case 1, except that FeS / Fe3O4@C with a mass ratio of sodium alginate to carbon black of 20:1 was prepared. When this catalyst was used as the cathode, the removal of tetracycline was 72% in 2 hours. The results are shown in Figure 6 .
[0017] Implementation Case 5 After the CB-800 and FeS@C were physically and mechanically mixed in a ratio of 10:1 by calcining carbon black in a tube furnace in the same way as the FeS / Fe3O4@C catalyst, the FeS / Fe3O4@C catalyst prepared in Example 1 was compared with the FeS / Fe3O4@C catalyst prepared in the rotating disk electrode test. It was found that the prepared FeS / Fe3O4@C catalyst exhibited a good electron transfer process, and the calculated H2O2 selectivity was more than 90%. The results are shown in Figure 7 , while the H2O2 selectivity of CB-800 and FeS@C mechanical mixed catalysts was only 76%, indicating that FeS / Fe3O4@C is a good catalyst for achieving two-electron ORR to produce H2O2.
[0018] refer to Figure 8 When the mechanically mixed catalyst of CB-800 and FeS@C was used as the cathode, the tetracycline removal was only 50%, and the removal of tetracycline by electrosorption and carbon felt substrate alone was only 8.6% and 30.2%, respectively. Meanwhile, the iron dissolution rate was reduced from 0.18 mg L -1 Increased to 2.16 mg L -1 These indicate that the FeS / Fe3O4@C cathode prepared in the present invention is a good dual-functional cathode that can catalyze the decomposition of in-situ generated H2O2 into active oxygen species, thereby achieving the removal of pollutants.
[0019] Implementation Case 6 The steps of implementation case 6 are basically the same as those of implementation case 1. The effects of adding different inhibitors to the catalytic reaction system on the generation of free radicals in the system are compared without adding pollutants. Fig. 9 It can be observed that after adding TBA or N2 to replace O2, • OH signal disappears, after adding SOD and CAT • The decrease of OH signal indicates that in this system, H2O2 and • O2 − All produced • OH. However, H2O2 is not produced 1 The main source of O2, because after adding CAT, 1 O2 has no obvious change. • When OH is captured by TBA, 1The signal of O2 increases. Therefore, it can be considered that O2 and • O2 − is produced 1 O2 source, O V Can promote • O2 − Generation of free radicals.
[0020] Implementation Case 7 The steps of implementation case 7 are basically the same as those of implementation case 1, using PMSO as a probe to investigate the presence of Fe(IV). • OH or Fe(IV) species, so different initial pH values were adjusted to verify the degradation of PMSO by FeS / Fe3O4@C cathode. Fig.10 In order to study the role of Fe(IV), the conversion rate of PMSO2 was calculated by the ratio of PMSO2 generation to PMSO consumption. It can be found that the PMSO2 conversion rate is below 40% at pH = 3-7, while the PMSO2 conversion rate is greater than 43.7% at pH = 9 and greater than 52.6% at pH = 11, indicating that Fe(IV) is easily formed at high pH values in this system.
[0021] Implementation Case 8 The steps of implementation case 8 are basically the same as those of implementation case 1. Fig. 9 When the FeS / Fe3O4@C cathode was reused 10 times, the removal of tetracycline could still reach 87%, and the dissolved iron concentration was lower than 0.18 mg L -1 ( Fig.10 ). Therefore, it is shown that the FeS / Fe3O4@C cathode can be reused and can reduce iron dissolution, thereby reducing the generation of iron sludge.
[0022] The above is only an implementation example of the present invention and does not limit the present invention in any form. Any ordinary technician in the industry can successfully implement the present invention as shown in the drawings and above. However, any technician familiar with the profession can make some changes, modifications and evolutions of the contents shown above without departing from the scope of the technical solution of the present invention, which are all equivalent implementation examples of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above implementation examples based on the essential technology of the present invention are within the protection scope of the technical solution of the present invention.
Claims
1. Preparation and application of FeS-loaded Fe3O4 cathode wrapped with alginate-derived carbon shell, characterized by the following steps: (1) 20 g / L sodium alginate and carbon black were mixed and stirred at a mass ratio of 5:1 to 20:1, and then added into a 20 g / L ferrous sulfate heptahydrate solution at a volume ratio of 1:2, and the obtained composite gel was freeze-dried at a temperature of -40 °C; (2) The composite gel obtained in step (1) is placed in a tubular furnace under argon protection for pyrolysis, the temperature is increased to 400°C at a rate of 3-5°C / min, and the temperature is kept constant for 1.5-2.5 h, and then the temperature is increased to 800°C at a rate of 8-12°C / min, and the temperature is kept constant for 1.5-2.5 h to obtain an alginate-derived carbon shell-wrapped Fe3O4 catalyst FeS / Fe3O4@C loaded with FeS.
2. The preparation and application of a FeS-loaded alginate-derived carbon shell-wrapped Fe3O4 cathode according to claim 1, characterized in that: The catalyst powder of claim 1 was weighed into a mixed solution of ethanol and water in a ratio of 1:1, and 20% PTFE emulsion was added and shaken to mix evenly, and the loading amount was controlled to be 15-20 mg cm -1 It is loaded on the substrate electrode, and after natural drying, it can be used as a cathode by calcining at 360 °C in a tube furnace for 30 min. The pH of the wastewater to be treated is adjusted to 3-11, and the cathode potential is controlled to -0.2 V - 0.5 V relative to the reversible hydrogen electrode for heterogeneous electro-Fenton degradation.
3. The preparation and application of a FeS-loaded alginate-derived carbon shell-wrapped Fe3O4 cathode according to claim 2, characterized in that The carbon substrate is carbon felt, carbon cloth, carbon paper or carbon fiber.
Citation Information
Patent Citations
Sodium ion battery anode material FeS2 / Fe3O4 / C and preparation method of same
CN107507978A
Preparation method and application of iron-loaded sodium alginate carbon aerogel
CN109850865A
Carbon aerogel for improving divalent Fe reducibility and hydrogen peroxide yield in electrode as well as preparation method and application thereof
CN111320241A
Preparation of Fe3O4@C confinement interface loaded Ce-MOFs catalyst and application thereof in electro-Fenton
CN113275040A
Preparation method and application of chitosan-coated electro-Fenton cathode
CN114368807A
Cited By
Boron-doped cobalt-loaded carbon-based catalyst as well as preparation method and application thereof
CN122538127A
